التخطيط الأسرى في ضوء القرآن الكريم - مسكري، نصري بنت جابر (al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2006)
This study aims to underline the importance of planning and family planning in particular; and how planning does not contradict the notion of AL Tawakul, relying on Allah. The study demonstrates how the holy Qur’an has greatly emphasized on planning in family affairs. The Qur’anic method of planning covers all aspects of family affairs. The thesis, also, relates the Qur’anic method of planning to the contemporary family planning method. At the methodological aspects, the study applies three different methods of analysis. It uses inductive method to underline Qur’an stories in which planning have been generally addressed and verses related to family planning in particular. The thesis uses the same method to gather from heritage of Tafsir, translations of verses related to the topic. The study also applies analytical method, to analyze related verses to planning and Quranic method of family planning. Deductive method is also used to deduct educational lessons that can be learned from family planning. The study emphasizes that planning plays great role in the life of individual, family and community as a whole. Thus, planning does not contradict with the notion of AL Tawakul. Planning is however means to get things done, which is also one of the greatest ways of AL Tawakul. Prophets (PBUT) were great planers in conveying the message. Prophet Muhammad (s.a.w) in particular planned to protect Islamic Da’wah, and establish an Islamic State. Furthermore, the holy Qur’an has given great importance to the notion planning in family affairs, through careful coordination of those matters, decentralization of tasks and clarification of rights and responsibilities. In addition, the holy Qur’an highlights the necessary process that need to be taken in maintaining peaceful atmosphere within the family. This is to achieve higher level of success and happiness for family constitution. Finally the contemporary family planning refers to the achievement of future visions and goals of the family in all aspects; including educational and economic ones.